Introduction to the Special Issue on GaLA Conf 2021 - Francesca De Rosa; Jannicke Baalsrud Hauge; Pierpaolo Dondio; Iza Marfisi-Schottman; Margarida Romero; Francesco Bellotti (Serious Games Society, 2022)
This is a short introduction pecial issue of the International Journal of Serious Games dedicated to the selected best papers of the 2021 edition of the Games and Learning (GALA) 2021 conference. The three selected papers have undergone a regular review process. Covered topics range from cooperative games to mixed reality, from digital companions to game co-design.